Respostas

  • Usuário do Brainly
2014-05-22T22:39:42-03:00
(x + 3)² = 2x . (x + 7)
(x + 3) . (x + 3) = 2x . (x + 7)
x² + 3x + 3x + 9 = 2x² + 14x
x² + 6x + 9 = 2x² + 14x
x² - 2x² + 6x - 14x + 9
- x² - 8x + 9 = 0
Δ = b² - 4 . a . c
Δ = (- 8)² - 4 . (- 1) . 9
Δ = 64 + 36
Δ = 100

x = (- b 
± √Δ)/2 . a
x = (- (- 8) ± √100)/2 . (- 1)
x = (8 ± 10)/- 2

x' = (8 + 10)/- 2
x' = 18/- 2
x' = - 18/2
x' = - 9

x'' = (8 - 10)/- 2
x'' = - 2/- 2
x'' = 2/2
x'' = 1
1 5 1
pode resumir não? rsrsrs grandão, mas obg